(untitled) (European Journal of Economics, Finance and Business Development, 2025)
The article presents an examination of foreign experience in creating and operating a management system for public-private partnership projects. The study presents the most successful practices in the development of public-private partnerships. The analysis of practical experiences in the domain of public-private partnerships led to the identification of the principal criteria for the success of public management systems for such projects. The identified criteria were then used to consider the possibilities of improving public-private partnership mechanisms in selected areas in the Republic of Uzbekistan. Furthermore, the implementation of public-private partnerships in the further development of the railway passenger transportation sector was contemplated.